Recycled EVA supercritical foaming sole and preparation method thereof
By cross-linking EVA with a DA structure, a recycled EVA supercritical foam sole can be formed that can be processed multiple times, solving the environmental and recycling problems of traditional EVA materials, realizing the recyclability and excellent mechanical properties of the materials, and being suitable for shoe materials manufacturing.
Patent Information
- Application Number
- CN202510093259.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional EVA materials have problems such as difficult to degrade in the environment, dependence on petroleum resources and difficulty in recycling, especially in shoe materials manufacturing, which is difficult to meet the water resistance performance requirements.
EVA is crosslinked with a DA structure to form a recycled EVA supercritical foam sole that can be processed multiple times. Combined with OBC, SEBS, fillers and wear-resistant agents, the crosslinking structure is reversed through high-temperature DA reaction to achieve material recyclability and excellent mechanical properties.
It realizes the ability of EVA materials to be processed and recycled multiple times, and at the same time improves the mechanical properties and weather resistance of the sole. It is suitable for shoe material manufacturing and avoids the environmental pollution problems of traditional EVA materials.
Smart Images

Figure CN119798831A_ABST
Abstract
Description
[0001] The invention belongs to the technical field of foaming materials, and particularly relates to a recycled EVA supercritical foaming sole and a preparation method thereof. Background Art
[0002] With the rapid development of economy and technology, my country has become the largest country in shoe manufacturing and production, with an annual production capacity of over 3 billion pairs of shoes. In 1974, Brooks first used a revolutionary polymer material - EVA (ethylene-vinyl acetate copolymer). Due to its light weight and obvious shock absorption effect, it quickly replaced rubber and became the most widely used midsole material.
[0003] Although EVA materials have many advantages, traditional EVA materials have some environmental problems: EVA materials are difficult to degrade in the natural environment, resulting in long-term accumulation of landfills; the production of EVA consumes a large amount of petroleum resources, increasing dependence on non-renewable resources; after the service life of EVA products ends, how to deal with these materials becomes a problem. After EVA materials are chemically or physically cross-linked, covalent bonds or hydrogen bonds are formed between EVA molecules and the molecular chains of the blended polymer or the molecules of inorganic fillers, so that the original linear structure of the material is transformed into a network structure, thereby changing the structure and properties of the original polymer. Compared with the recyclability of thermoplastics, thermosetting polymers are difficult to dissolve and melt due to their cross-linked network structure, making them difficult to recycle. Some recycling processes are even more expensive than producing new materials, such as through chemical recycling and biodegradation; the current main way to recycle EVA is to crush EVA waste particles and mix them with original EVA particles in a certain proportion for reuse. However, repeated processing causes mechanical degradation or thermal decomposition of EVA, which ultimately leads to a decrease in material performance. Moreover, due to the poor compatibility between cross-linked milled EVA and the original EVA raw material, it can only be replaced at a lower addition ratio, limiting its scope of use. In the literature Macromolecules 2020, 53, 458−464, triethyl borate was used to dynamically cross-link EVA through an ester exchange mechanism to obtain an EVA-like glass with a reversible cross-linked structure. The EVA material cross-linked with borate has good mechanical properties and recyclability, but its water resistance is poor, so it is difficult to be used in shoe manufacturing. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a recycled EVA supercritical foaming sole that can be processed multiple times and a preparation method thereof, wherein the EVA is cross-linked with an auxiliary cross-linking agent having a DA structure, so that the material has excellent mechanical properties and is recyclable.
[0005] The technical solution for achieving the purpose of the present invention is as follows: A recycled EVA supercritical foaming sole comprises the following raw materials in parts by weight: 60-70 parts of EVA, 8-12 parts of OBC, 8-12 parts of SEBS, 0.5-1 part of a cross-linking agent, 1.5-2.5 parts of an auxiliary cross-linking agent, 8-12 parts of a filler and 8-12 parts of an anti-wear agent; the auxiliary cross-linking agent has the following molecular structure: .
[0006] The cross-linking agent used in the present invention has four carbon-carbon double bonds when cross-linking EVA, two of which are double bonds on the ring and double bonds in dimethylvinylsiloxane as shown in the above molecular structure diagram, and the other two are double bonds in the furan and maleimide structures generated by the reverse reaction of the DA structure of the cross-linking agent at high temperature during processing, as shown in the attached Figure 2 As shown in ; among them, the furan and maleimide double bonds are conjugated double bonds on the ring, which are relatively stable; the double bonds on the ring shown in the above molecular structure diagram reduce the probability of free radical attack due to the rigidity and steric hindrance of the double ring structure. Therefore, during the processing, the free radicals mainly attack the double bonds in the dimethylvinylsiloxane outside the ring.
[0007] Preferably, the crosslinking agent is one or more of diisopropylbenzene peroxide, di-tert-butyl peroxyisopropylbenzene, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane and tert-amyl peroxide (2-ethylhexyl) carbonate; the filler is one or more of talc, barium sulfate and titanium dioxide; and the wear-resistant agent is a polysiloxane with a viscosity of 1000 to 10000 cSt.
[0008] Preferably, the content of vinyl acetate in the EVA is 15wt% to 25wt%.
[0009] It should be noted that the auxiliary cross-linking agent used in the present invention can be synthesized by a variety of methods. The following is only one method for synthesizing the auxiliary cross-linking agent used in the present invention, and is not the only method.
[0010] Preferably, the preparation method of the auxiliary cross-linking agent is as follows: S1.1 eq of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is aminated with 2-10 eq of maleic anhydride and then dehydrated to form a bismaleimide containing a siloxane structure; S2. Reaction of 1 eq of the bismaleimide containing a siloxane structure obtained in step S1 with 2 to 2.5 eq of furfuryl alcohol by DA to obtain a compound; S3. 1 eq of the compound obtained in step S2 is reacted with 5-10 eq of dimethylvinylchlorosilane to obtain a co-crosslinking agent.
[0011] Specifically, the detailed steps of S1 in the preparation method of the auxiliary cross-linking agent are as follows: dissolving 1 eq of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 2-10 eq of maleic anhydride in a toluene solution, reacting in a reactor at 20-30 °C under a nitrogen atmosphere for 1-2 h to obtain a mixture; adding 4-10 eq of zinc chloride to the mixture, heating to 70-80 °C, and then dripping a toluene solution containing 8-10 eq of hexamethyldisilazane, and after the dripping is completed, heating to 100-120 °C, reacting for 2-3 h, cooling to room temperature, filtering the obtained mixture, removing solid insolubles, and washing the solution with dilute hydrochloric acid solution, saturated sodium bicarbonate solution and saturated sodium chloride solution at least twice each, collecting the organic phase, and removing the solvent by vacuum rotary evaporation to obtain a bismaleimide containing a siloxane structure.
[0012] Specifically, the detailed steps of S2 in the preparation method of the auxiliary cross-linking agent are: Under a nitrogen atmosphere, 1 eq of the bismaleimide containing a siloxane structure obtained in step S1 and 2-2.5 eq of furfuryl alcohol were added to a reaction kettle and dissolved in toluene. The mixture was reacted at a temperature of 50-80 °C for 1-3 h. After the reaction was stopped, the solvent was removed and the obtained product was washed with cold methanol at least twice to obtain a compound.
[0013] Specifically, the detailed steps of S3 in the preparation method of the auxiliary cross-linking agent are: Under a nitrogen atmosphere, add 1 eq of the compound obtained in step S2, 4-10 eq of dimethylvinylsilyl chloride and 5-10 eq of triethylamine dispersed in dichloromethane into a reaction kettle, stir for 2-3 h at a temperature of 25-60 °C, wash with a dilute hydrochloric acid solution and a saturated sodium bicarbonate solution at least twice each, remove the solvent, and obtain a cross-linking agent.
[0014] The present invention also discloses a preparation method for recycling EVA supercritical foaming soles, comprising the following steps: Step 1, premixing EVA, OBC, SEBS, a crosslinking agent, a co-crosslinking agent, a filler, and an anti-wear agent in a high-speed mixer to obtain a composition; Step 2, granulating the composition obtained in step 1, and then injection molding at an injection molding temperature of 80 to 130 ° C. and a mold temperature of 150 to 200 ° C., holding the pressure for 200 to 800 seconds to prepare a shoe embryo; Step 3. Finally, the shoe blank obtained in step 2 is placed in a CO2 supercritical reactor for foaming, the CO2 pressure is controlled at 7-15 MPa, the foaming temperature is 35-80 °C, the pressure is released after the heat and pressure holding time is 1-2 h, and the shoe blank is taken out and cooled to room temperature to obtain a finished shoe sole.
[0015] Beneficial Effects The present invention includes the following beneficial effects: using a cross-linking agent with a DA structure to cross-link EVA, the material has excellent mechanical properties and recyclability. The cross-linking agent with a DA structure does not need to be modified and grafted to EVA in advance, which simplifies the process flow. The cross-linking agent used has a DA structure, and can transform the cross-linked EVA structure into a linear structure through the reverse reaction of the DA reaction at high temperature, so that it has excellent processing performance and recyclability; the molecular structure of the cross-linking agent used is Si-OC, Si-O-Si, rigid bicyclic and imide structure, with good mechanical and weather resistance, and the overall structure is soft (Si-OC)-hard (rigid bicyclic and imide structure)-soft (Si-O-Si)-hard (rigid bicyclic and imide structure)-soft structure (Si-OC), which improves the mechanical properties of the shoe material after cross-linking while maintaining the softness and comfort of the shoe material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The schematic diagram of the synthesis route and molecular structure of the cross-linking agent of the present invention; Figure 2 Schematic diagram of the mechanism of cross-linking EVA by the cross-linking aid of the present invention; Figure 3 It is the NMR spectrum of the cross-linking agent of the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0019] The raw materials and equipment used in the embodiments and comparative examples are described as follows: EVA: vinyl acetate content 18%, brand 7350M, Formosa Plastics Corporation; OBC: Brand 9077, Dow Chemical, USA; SEBS: Brand 7551, Lee Chang Jung Rubber Co., Ltd. Cross-linking agent: di-tert-butyl peroxyisopropylbenzene, product number HY25155-25-3, Changzhou Hongyu Chemical Co., Ltd. Filler: talcum powder, 300~400 mesh, Shandong Linyi Haotian Talc Powder Factory; Wear-resistant agent: polysiloxane, viscosity 10000 cSt, Jinan Longcheng Silicone Co., Ltd.; 1,3-Bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane: Product No. W830187, Anaiji Chemical; Maleic anhydride: Product No. A010576, Anaiji Chemical; Hexamethyldisilazane: Product No. D020051, Anaiji Chemical; Furfuryl alcohol: Product No. W330027, Anaiji Chemical; Dimethylvinylchlorosilane: Product No. W330153, Anaiji Chemical; Tetramethyldivinyldisiloxane (TMVDS): Product No. BD54273, Shanghai BiDe.
[0020] Cross-linking agent (self-made) S1. 1 eq of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 3 eq of maleic anhydride were dissolved in a toluene solution, and reacted in a reactor at 25°C under a nitrogen atmosphere for 1 h to obtain a mixture; 4 eq of zinc chloride was added to the mixture, and the mixture was heated to 80°C, and a toluene solution containing 10 eq of hexamethyldisilazane was added dropwise. After the addition was completed, the mixture was heated to 120°C, reacted for 2 h, cooled to room temperature, and the obtained mixture was filtered to remove solid insolubles. The solution was washed with a dilute hydrochloric acid solution, a saturated sodium bicarbonate solution, and a saturated sodium chloride solution for 3 times each, and the organic phase was collected and the solvent was removed by vacuum rotary evaporation to obtain a bismaleimide containing a siloxane structure.
[0021] S2. Under a nitrogen atmosphere, add 1 eq of bismaleimide containing a siloxane structure obtained in step S1 and 2 eq of furfuryl alcohol into a reaction kettle and dissolve them in toluene. React at 50°C for 2 h. After stopping the reaction, remove the solvent, and wash the product with cold methanol three times to obtain a compound.
[0022] S3. Under a nitrogen atmosphere, add 1 eq of the compound obtained in step S2, 4 eq of dimethylvinylsilyl chloride and 5 eq of triethylamine into a reaction kettle and disperse them in dichloromethane. Stir for 3 h at 40 °C, then wash with dilute hydrochloric acid solution and saturated sodium bicarbonate solution three times each, remove the solvent, and obtain a cross-linking agent.
[0023] A preparation method for recycling EVA supercritical foaming soles comprises the following steps: Step 1, premixing EVA, OBC, SEBS, a crosslinking agent, a co-crosslinking agent, a filler, and an anti-wear agent in a high-speed mixer to obtain a composition; Step 2, granulating the composition obtained in step 1, and then injection molding at an injection molding temperature of 120 ° C and a mold temperature of 160 ° C, holding the pressure for 600 s to prepare a shoe embryo; Step 3. Finally, the shoe blank obtained in step 2 is placed in a CO2 supercritical reactor for foaming, the CO2 pressure is controlled at 8MPa, the foaming temperature is 50°C, the pressure is released after the heat and pressure holding time is 1h, and the shoe blank is taken out and cooled to room temperature to obtain a finished shoe sole.
[0024] Table 1 Formula of EVA supercritical foaming sole (kg)
[0025] A comparative experiment was conducted using TMVDS as a substitute for the co-crosslinking agent.
[0026] The following is the test method of the performance parameters involved in the present invention: Hardness: Tested according to standard HG / T 2489 2007; Impact rebound: tested according to standard GB / T 1681-2009; DIN abrasion: tested according to ASTM D1044-19; Tensile strength: tested according to standard GB / T 528-2009; Elongation at break: tested according to standard GB / T 528-2009; Recyclability: The soles were crushed, re-injected and foamed four times in total. The impact rebound, tensile strength and elongation at break were tested.
[0027] Table 2 Performance test of EVA supercritical foaming sole
[0028] It should be noted that the values shown in the "Original" column in the table are absolute values of the test data, and the data shown in the "Recycled" column in the table are the ratios of the values of the performance data after recycling 4 times to the original measured values.
[0029] As shown in Table 2, Examples 3 to 5, with the increase in the amount of the co-crosslinking agent, except that the material hardness changes slightly, the other physical properties are all improved, and the recovery performance is also gradually improved compared to the original performance. As shown in the data of Comparative Example 1, when the co-crosslinking agent of the present invention is not added, the material physical properties and recovery performance are all poor. As shown in the data of Comparative Example 2, the hardness of the co-crosslinking agent of the present invention is large, which has a certain effect on the comfort of the shoes, and the tensile strength and elongation at break are reduced. As shown in the data of Comparative Example 3, after the co-crosslinking agent is replaced with tetramethyl divinyl disiloxane, its mechanical properties are relatively excellent, but the hardness is high and the recovery performance is poor.
[0030] Therefore, the recycled EVA supercritical foaming sole provided by the present invention has good mechanical properties and recyclability.
[0031] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A recycled EVA supercritical foaming sole, characterized in that , by weight, including the following raw materials: 60-70 parts of EVA, 8-12 parts of OBC, 8-12 parts of SEBS, 0.5-1 parts of cross-linking agent, 1.5-2.5 parts of auxiliary cross-linking agent, 8-12 parts of filler and 8-12 parts of wear-resistant agent; the auxiliary cross-linking agent has the following molecular structure: 。 2. A recycled EVA supercritical foaming sole as claimed in claim 1, characterized in that: The crosslinking agent is one or more of dicumyl peroxide, di-tert-butyl peroxycumene, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane and tert-amyl peroxide (2-ethylhexyl) carbonate; the filler is one or more of talc, barium sulfate and titanium dioxide; and the wear-resistant agent is polysiloxane with a viscosity of 1000 to 10000 cSt.
3. A recycled EVA supercritical foaming sole as claimed in claim 1, characterized in that: The content of vinyl acetate in the EVA is 10wt% to 60wt%.
4. A recycled EVA supercritical foaming sole as claimed in claim 1, characterized in that: The preparation method of the cross-linking aid is as follows: S1.1 eq of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is aminated with 2-10 eq of maleic anhydride and then dehydrated to form a bismaleimide containing a siloxane structure; S2. Reaction of 1 eq of the bismaleimide containing a siloxane structure obtained in step S1 with 2 to 2.5 eq of furfuryl alcohol by DA to obtain a compound; S3. 1 eq of the compound obtained in step S2 is reacted with 4 to 10 eq of dimethylvinyl chlorosilane to obtain a co-crosslinking agent.
5. A recycled EVA supercritical foaming sole as claimed in claim 4, characterized in that: The detailed steps of S1 in the preparation method of the auxiliary cross-linking agent are as follows: dissolving 1 eq of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 2-10 eq of maleic anhydride in a toluene solution, reacting in a reactor at a temperature of 20-30°C and a nitrogen atmosphere for 1-2 h to obtain a mixture; adding 4-10 eq of zinc chloride to the mixture, heating the mixture to 70-80°C, and then dripping a toluene solution containing 8-10 eq of hexamethyldisilazane, and after the dripping is completed, heating the mixture to 100-120°C, reacting for 2-3 h, cooling the mixture to room temperature, filtering the obtained mixture, removing solid insolubles, and washing the solution with a dilute hydrochloric acid solution, a saturated sodium bicarbonate solution, and a saturated sodium chloride solution at least twice each, collecting the organic phase, and removing the solvent by vacuum rotary evaporation to obtain a bismaleimide containing a siloxane structure.
6. A recycled EVA supercritical foaming sole as claimed in claim 4, characterized in that: The detailed steps of S2 in the preparation method of the auxiliary cross-linking agent are: Under a nitrogen atmosphere, 1 eq of the bismaleimide containing a siloxane structure obtained in step S1 and 2-2.5 eq of furfuryl alcohol were added to a reaction kettle and dissolved in toluene. The mixture was reacted at a temperature of 50-80 °C for 1-3 h. After the reaction was stopped, the solvent was removed and the obtained product was washed with cold methanol at least twice to obtain a compound.
7. A recycled EVA supercritical foaming sole as claimed in claim 4, characterized in that: The detailed steps of S3 in the preparation method of the auxiliary cross-linking agent are: Under a nitrogen atmosphere, add 1 eq of the compound obtained in step S2, 5-10 eq of dimethylvinylsilyl chloride and 5-10 eq of triethylamine dispersed in dichloromethane into a reaction kettle, stir for 2-3 h at a temperature of 25-60 °C, wash with a dilute hydrochloric acid solution and a saturated sodium bicarbonate solution at least twice each, remove the solvent, and obtain a cross-linking agent.
8. A method for recovering EVA supercritical foaming soles as described in any one of claims 1 to 7, characterized in that, The following steps are involved: Step 1, premixing EVA, OBC, SEBS, a crosslinking agent, a co-crosslinking agent, a filler, and an anti-wear agent in a high-speed mixer to obtain a composition; Step 2, granulating the composition obtained in step 1, and then injection molding at an injection molding temperature of 80 to 130 ° C. and a mold temperature of 150 to 200 ° C., holding the pressure for 200 to 800 seconds to prepare a shoe embryo; Step 3. Finally, the shoe blank obtained in step 2 is placed in a CO2 supercritical reactor for foaming, the CO2 pressure is controlled at 7-15 MPa, the foaming temperature is 35-80 °C, the pressure is released after the heat and pressure holding time is 1-2 h, and the shoe blank is taken out and cooled to room temperature to obtain a finished shoe sole.
Citation Information
Cited By
Recyclable foaming sole material and preparation method thereof
CN121293572A